2013
DOI: 10.1021/jp407425y
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Activity of BN Codoped Graphene Oxide Derived from Carbon Dioxide

Abstract: The formation of boron and nitrogen (BN) codoped graphene oxide (GO) from carbon dioxide (CO2) was accomplished using ammonia borane (NH3BH3) as a reducing agent. This graphene-based material was produced in two sequential processes (carbon fixation and pyrolysis) under moderate reaction conditions. One important potential application for the graphene-based material is as catalysts for oxygen reduction reaction (ORR) in fuel cell electrodes. This utilization is supported by the fact that B and N are incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…139 Experimentally, BNG has been synthesized using various methods. [140][141][142][143][144][145] Antonietti's group has reported an in situ pyrolytic synthesis of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 holey BNG monoliths by direct copolymerization of glucose and boric acid in the interlayer spaces of lamellar carbon nitride. 140 Based on the XPS analysis, ~16 at.% of doped N is in the form of pyridinic and graphitic-N and the N-B bonds were detected too; while the doped B atoms appear mainly in the C-B and N-B bonds and to smaller degree in the B-O bonding with a doping level of 14 at.%.…”
Section: B and N-doped Graphene (Bng) Through Dft Calculations Sen mentioning
confidence: 99%
See 1 more Smart Citation
“…139 Experimentally, BNG has been synthesized using various methods. [140][141][142][143][144][145] Antonietti's group has reported an in situ pyrolytic synthesis of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 holey BNG monoliths by direct copolymerization of glucose and boric acid in the interlayer spaces of lamellar carbon nitride. 140 Based on the XPS analysis, ~16 at.% of doped N is in the form of pyridinic and graphitic-N and the N-B bonds were detected too; while the doped B atoms appear mainly in the C-B and N-B bonds and to smaller degree in the B-O bonding with a doping level of 14 at.%.…”
Section: B and N-doped Graphene (Bng) Through Dft Calculations Sen mentioning
confidence: 99%
“…Nevertheless, Lee et al reported the origin of the ORR catalytic activity could be the insertion of B and N atoms as BCO 2 and pyrrolic-N. 142 Tour's group synthesized B and N co-doped GQD/graphene hybrid, which combined the advantages of both components, such as abundant edges and doping sites, high electrical conductivity and high surface area, leading to higher ORR activity than that of Pt/C in alkaline media. We reported a mesoporous SNG as the ORR catalyst (Figure 10a), which displayed a positive onset potential of -0.06 V vs Ag/AgCl, the n value between 3.3-3.6, as well as high J K exceeding that of Pt/C at -0.6 V (the as-prepared samples and commercial Pt/C were measured in the same 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 electrochemical system under the same conditions, Figure 10b-d).…”
Section: Bng Basedmentioning
confidence: 99%
“…TMPP-C-500 and TMPP-C-500/50 had a higher graphitic N portion than the pyridinic and pyrrolic N states, whereas the relative ratios of pyridinic and pyrrolic N in FeTMPP-C-50, FeTMPP-C-500, and FeTMPP-C-500/50 increased, compared to TMPP-C-500 and TMPP-C-500/50, due to the metal doping forming Fe-N 4 or Fe-N 3 macrocycles among the nitrogen species [50,51]. The Fe-N x macrocycles in the FeTMPP-C-50, FeTMPP-C-500, and FeTMPP-C-500/50 might withdraw an electron, thus resulting in an enhancement of positively charged carbon atoms [52,53]. The charge polarization and bimodal pore structure can adsorb and reduce the O 2 species on the surfaces in the doped carbon samples accompanied by a complete transferred electron reaction [54,55].…”
Section: Resultsmentioning
confidence: 99%
“…The value of n represents the number of electrons transferred per oxygen molecule, and can be calculated from B by using Eqs. (1) and (2) and parameters [16]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%